2004
DOI: 10.1021/jm0494826
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase Inhibitors:  Synthesis and Inhibition of Cytosolic/Membrane-Associated Carbonic Anhydrase Isozymes I, II, and IX with Sulfonamides Incorporating Hydrazino Moieties

Abstract: Targeting proteins overexpressed in hypoxic tumors is as an important means of controlling cancer disease. One such protein is the carbonic anhydrase (CA) isoenzyme IX, which in some types of tumors is overexpressed 150-200-fold. We report here a series of sulfonamide derivatives, prepared from 2-carbohydrazido- and 4-carbohydrazido-benzenesulfonamides, which were further derivatized by reaction with aryl isocyanates or arylsulfonyl isocyanates. Several low nanomolar CA IX inhibitors were detected in this way.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 28 publications
3
57
0
Order By: Relevance
“…Flourophenylsulphamate adducts were reported that the sulphomates possess a rather variable binding pattern within the hCA active site 42,43 . It should also be mentioned that among the nitro substituted compounds, o-nitro substituted compound (5i) seems to be much less effective inhibitors as compared to the meta (5j) 44 , this may be due to the sterical impairment of the ortho-substituent for the binding of the compounds to the Zn(II) ion within the enzyme active site. K i values of the compounds for hCA I (K i ¼ 0.33-1.21) are close to the clinically used sulfonamide AZA (acetazolamide, K i ¼ 0.250 mM) whereas the values of the compounds for hCA II (K i ¼ 0.11-1.99 mM) are higher than AZA (K i ¼ 0.012 mM) 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Flourophenylsulphamate adducts were reported that the sulphomates possess a rather variable binding pattern within the hCA active site 42,43 . It should also be mentioned that among the nitro substituted compounds, o-nitro substituted compound (5i) seems to be much less effective inhibitors as compared to the meta (5j) 44 , this may be due to the sterical impairment of the ortho-substituent for the binding of the compounds to the Zn(II) ion within the enzyme active site. K i values of the compounds for hCA I (K i ¼ 0.33-1.21) are close to the clinically used sulfonamide AZA (acetazolamide, K i ¼ 0.250 mM) whereas the values of the compounds for hCA II (K i ¼ 0.11-1.99 mM) are higher than AZA (K i ¼ 0.012 mM) 26 .…”
Section: Resultsmentioning
confidence: 99%
“…40 We reported recently a series of sulfonamide derivatives incorporating hydrazine moiety in their structure, prepared from 2-carbohydrazido-and 4-carbohydrazido-benzenesulfonamides, which were further derivatized by reaction with aryl isocyanates or arylsulfonyl isocyanates. 44 The hydrazine moiety was considered in this study to be beneficial for CA IX targeting compounds, for several reasons: (i) the facile synthesis and subsequent derivatization of such compounds, leading to a chemical diversity necessary when such new targets are considered (ii) the hydrazine moiety is susceptible to redox chemistry which may be advantageous in the hypoxic environment present in some tumors. Several low nanomolar CA IX inhibitors were detected in this way.…”
Section: C a I X I N H I B I T O R S I N T H E S U L F O N A M I D mentioning
confidence: 99%
“…Reaction yields less than Ͻ1 g were purified with Varian mega bond elut (Palo Alto, CA) solid-phase extraction columns (normal phase silica). Building block 1 was synthesized from 4-carboxybenzene sulfonamide [42]. Aldehyde building blocks A-E were synthesized in two steps from commercially available amino acid methyl esters.…”
Section: Chemistrymentioning
confidence: 99%